Segmentally Demineralized Cortical Bone With Stem Cell-Derived Matrix Promotes Proliferation, Migration and Differentiation of Stem Cells in vitro - He, Shu-Kun; Ning, Liang-Ju; Hu, Ruo-Nan; Yao, Xuan; Cui, Jing; Ding, Wei; Luo, Jing-Cong; Qin, Ting-Wu (Frontiers in Cell and Developmental Biology, 2022)
A recent study has shown that demineralized cortical bone (DCB) does not improve the healing of tendon-bone interface. Considering that there is a gradient of mineral content in the tendon-bone interface, we designed a partially demineralized cortical bone (pDCB) scaffold with two different regions: undemineralized cortical bone section within the scaffold (pDCB-B) and complete demineralized cortical bone section within the scaffold (pDCB-D), to mimic the natural structure of the tendon-bone interface. Furthermore, the extracellular matrix (ECM) from tendon-derived stem cells (TDSCs) was used to modify the pDCB-D region of pDCB to construct a novel scaffold (pDCB-ECM) for enhancing the bioactivity of the pDCB-D. The surface topography, elemental distribution, histological structure, and surface elastic modulus of the scaffold were observed using scanning electron microscopy, energy-dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy, histological staining and atomic force microscopy. Cell proliferation of bone marrow mesenchymal stem cells (BMSCs) and TDSCs cultured on scaffolds was evaluated using the Cell Counting kit-8, and cell viability was assessed by Live/Dead cell staining. Cell morphology was detected by fluorescent staining. The ability of the scaffolds to recruit stem cells was tested using transwell migration assay. The expression levels of bone-, cartilage- and tendon-related genes and proteins in stem cells were assessed by the polymerase chain reaction and western blotting. Our results demonstrated that there was a gradient of Ca and P elements in pDCB, and TDSC-derived ECM existed on the surface of the pDCB-D region of pDCB. The pDCB-ECM could promote stem cell proliferation and migration. Moreover, the pDCB-B region of pDCB-ECM could stimulate osteogenic and chondrogenic differentiation of BMSCs, and the pDCB-D-ECM region of pDCB-ECM could stimulate chondrogenic and tenogenic differentiation of TDSCs when compared to DCB. Our study indicated that pDCB-ECM might be a potential bioscaffold to enhance the tendon-bone interface regeneration.